Beneficial Outcomes of Early Tracheostomy in Patients Requiring Prolonged Mechanical Ventilation - Samiei Nasr, Danial (Tanaffos, 2020)
BACKGROUND: Considering that tracheostomy is being done for huge amount of critically ill patients, the ideal time for this procedure is still controversial among different intensive care units (ICU). MATERIALS AND METHODS: 70 intubated patients were included in our study which was sorted into two subgroups: half of our patients received an early tracheostomy (ET) within 1–10 days post intubation and the rest received late tracheostomy (LT) within 11–21 days after getting intubated. RESULTS: 61.9% of the study population was male and the mean age was of 54 + 10.5 years. ET group mean Mechanical Ventilation (MV) duration was 8.11±4.9 days and was 16.3 ± 6.01 in the LT group (p<0.05) with a mean sedation duration of 6.1 ± 4.4 vs. 12.0 ± 6.5 (ET vs. LT) (p<0.05). Mean time of weaning process from ventilator was 2.7 ±2.3 for ET group and 5.5 ± 5.0 for LT group (p<0.05). The Mean ICU stay was 18.8 ± 2.2 in the ET group, and 22.1 ± 4.1 in the LT group (p: 0.98) at the same time. Length of stay at hospital for two group of patients did not show a meaningful difference (p= 0.279). CONCLUSION: Early tracheostomy decreases duration of mechanical ventilation and sedation use and more rapid weaning process in those patients who will require mechanical ventilation. Our findings revealed that tracheostomy timing has no significant impact on rate of hospital mortality and LOS at ICU and hospital.